Effect of dietary EPA and DHA on murine blood and liver fatty acid profile and liver oxylipin pattern depending on high and low dietary n6-PUFA. Issue 10 (8th October 2020) - Kutzner, Laura; Esselun, Carsten; Franke, Nicole; Schoenfeld, Kirsten; Eckert, Gunter P.; Schebb, Nils Helge
Abstract : A combination of n3-PUFA and low n6-PUFA feeding is most effective to decrease %n6 in HUFA and increase %EPA + DHA. Abstract : The intake of long-chain n3-polyunsaturated fatty acids (PUFA), which are associated with beneficial health effects, is low in the Western diet, while the portion of dietary n6-PUFA and hence the n6/n3-PUFA ratio is high. Strategies to improve the n3-PUFA status are n3-PUFA supplementation and/or lowering n6-PUFA intake. In the present study, mice were fed with two different sunflower oil-based control diets rich in linoleic (n6-high) or oleic acid (n6-low), either with low n3-PUFA content (∼0.02%) as control or with ∼0.6% eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA). The n6-low diet had only little or no effect on levels of arachidonic acid (ARA) and its free oxylipins in liver tissue. Supplementation with EPA or DHA lowered ARA levels with an effect size of n6-high < n6-low. Blood cell %EPA + DHA reached >8% and >11% in n6-high and n6-low groups, respectively. Elevation of EPA levels and EPA derived oxylipins was most pronounced in n6-low groups in liver tissue, while levels of DHA and DHA derived oxylipins were generally unaffected by the background diet. While the n6-low diet alone had no effect on blood and liver tissue ARA levels or n3-PUFA status, a supplementation of EPA or DHA was more effective in combination with an n6-low diet. Thus, supplementation of long-chain n3-PUFA combined with a reduction of dietary n6-PUFA is the most effective way to improve the endogenous n3-PUFA status.